Analysis of microRNA processing machinery gene (DROSHA, DICER1, RAN, and XPO5) variants association with end‐stage renal disease. Issue 12 (7th August 2020) - Fawzy, Manal S.; Abu AlSel, Baraah T.; Toraih, Eman A.
Abstract: Background: MicroRNA (miRNA) processing machinery gene variant was associated with several diseases. We aimed to explore for the first time the association of machinery gene ( DROSHA rs10719A/G; DICER1 rs3742330A/G; RAN rs14035C/T; and XPO5 rs11077T/G) variants with the susceptibility and phenotype of end‐stage renal disease (ESRD). Method: A total of 281 participants (98 ESRD patients and 183 healthy volunteers) were enrolled. Real‐Time TaqMan allelic discrimination assay was applied for the genotyping of the specified variants. Multiple logistic regression models, univariate, multivariate, and principal component analyses were carried out. Results: Carrying one DICER1 rs3742330*G allele conferred protection against developing ESRD [heterozygote comparison: OR = 0.30, 95% CI = 0.15‐0.62, dominant model: OR = 0.35, 95% CI = 0.17‐0.70]. Similarly, for XPO5 rs11077T/G, homozygote and heterozygote carriers of G variant were less likely to develop ESRD [homozygote comparison: adjusted OR = 0.23, 95% CI = 0.11‐0.50, and heterozygote comparison: OR = 0.50, 95% CI = 0.22‐0.92, and allelic model: OR = 0.46, 95% CI = 0.34‐0.70]. RAN rs14035*TT subjects were 5 times more likely to develop ESRD while being heterozygote (CT) have twice the risk [homozygote comparison: 5.18, 95% CI = 2.28‐11.8, heterozygote comparison: OR = 2.12, 95% CI = 1.10‐409]. Subgroup analysis also detected DICER1 rs3742330*A, XPO5 rs11077*T, and RAN rs14035*T as genetic risk determinants for ESRD development in both sex and age categories. Two genotype combinations of DROSHA/DICER1/XPO5 / RAN were associated with increased susceptibility to ESRD [A‐A‐T‐T: OR = 9.49, 95%CI = 2.48‐36.31 ( P = .001) and G‐A‐T‐T: OR = 5.92, 95%CI = 1.77‐19.83 ( P = .004), respectively]. Conclusion: Variants and combined genotypes of DICER1 rs3742330, XPO5 rs11077, and RAN rs14035 might be associated with ESRD development in the study population. Integrating molecular analysis in ESRD risk stratification is warranted. Abstract : The workflow of the study.